2009
DOI: 10.1007/s10704-009-9346-3
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive zone model and slow crack growth in ceramic polycrystals

Abstract: Ceramics polycrystals are subjected to slow crack growth (SCG) and also environmentally assisted failure, similarly to what is observed for glasses. The kinetics of fracture are known to be dependent on the load level, the temperature and also on the Relative Humidity (RH). However, evidences are available on the influence of the microstructure on the SCG rate with a marked increase in the resistance to the crack advance when comparing the response of a single crystal to that of a polycrystal. The clarificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The growth of cracks in heterogeneous materials is of crucial interest in many fundamental and industrial domains, and has been extensively studied using various numerical approaches, such as the finite element method (Zavattieri et al 2001;De la Osa et al 2009;Sancho et al 2007;Ruiz et al 2000;Itakura et al 2005), deformable lattice methods (Kitsunezaki 2013) and lattice element methods (Topin et al 2007;Affes et al 2012), to cite a few. Recently, the peridynamic approach emerged as an alternative method, based on integral equations, rather than partial differential equations (Silling 2000).…”
Section: Peridynamic Approachmentioning
confidence: 99%
“…The growth of cracks in heterogeneous materials is of crucial interest in many fundamental and industrial domains, and has been extensively studied using various numerical approaches, such as the finite element method (Zavattieri et al 2001;De la Osa et al 2009;Sancho et al 2007;Ruiz et al 2000;Itakura et al 2005), deformable lattice methods (Kitsunezaki 2013) and lattice element methods (Topin et al 2007;Affes et al 2012), to cite a few. Recently, the peridynamic approach emerged as an alternative method, based on integral equations, rather than partial differential equations (Silling 2000).…”
Section: Peridynamic Approachmentioning
confidence: 99%
“…The mechanism underlying SCG is described with a cohesive model that represents the reaction-rupture mechanism. A thermally activated formulation is adopted for the cohesive model which is presented by Romero de la Osa et al 4,5 It is shown that the formulation can capture the regime I and the load threshold that originates in the presence of initial stress related to the processing. In this section, a cohesive zone model (CZM) for the reaction-rupture mechanism underlying SCG in single and polycrystal ceramics is presented based on the description of SCG by Michalske and Freiman.…”
mentioning
confidence: 99%
“…These observations are formulated with a cohesive zone methodology. 4,5 A thermally activated cohesive model is proposed where the opening rate describing the damage kinetics is taken aṡ…”
mentioning
confidence: 99%
See 2 more Smart Citations